The Italian species of Pritha (Araneae, Filistatidae): a critical revision and description of two new species - Legittimo, Carlo Maria; Simeon, Enrico; Pompeo, Piergiorgio Di; Kulczycki, Alessandro (Zootaxa, 2017)
The species of Pritha Lehtinen, 1967 in Italy are revised for the first time, and a preliminary putative diagnosis for the genus is provided. Two new Italian species are described: Pritha parva sp. nov. (male and female) and P. sagittata sp. nov. (male and female). P. pallida (Kulczyński, 1897) and the type species P. nana (Simon, 1868) are entirely re-described. The copulatory organs, some other somatic characters and the habitus of each sex of the four Italian species are illustrated and photographed at high magnifications. P. debilis (Simon, 1911) and P. vestita (Simon, 1873) are removed from the synonymy with P. nana and revalidated to species status, and a lectotype is designated for the latter. P. pallida is recorded from Spain and Greece for the first time. Distribution, behavioural aspects and ecology of the four Italian species are discussed and photographs of live specimens, webs and habitats are provided.